2005
DOI: 10.1159/000088191
|View full text |Cite
|
Sign up to set email alerts
|

Approximal Caries Development in Adolescents with Low to Moderate Caries Risk after Different 3-Year School-Based Supervised Fluoride Mouth Rinsing Programmes

Abstract: The aim was to evaluate a 3-year randomised controlled trial of school-based fluoride mouth rinsing (FMR) on approximal caries development in 13- to 16-year-olds with low to moderate caries risk. The adolescents used F toothpaste at home and underwent prophylactic treatment at yearly check-ups at public dental clinics. Out of 788 randomly selected 13-year-olds, 622 completed the trial, carried out in 1999–2003. Supervised by a dental nurse, the subjects rinsed with a 0.2% NaF solution at different intervals. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…Even then attrition could not be controlled at the end of 1 year. This finding of attrition rate was less when compared to study done by Moberg Sköld et al [31] who reported a drop-out of 21% at the end of 3 years. The reason for such high drop-out is due to the change in schools during the promotion to the class grade and duration of the study.…”
Section: Discussioncontrasting
confidence: 66%
“…Even then attrition could not be controlled at the end of 1 year. This finding of attrition rate was less when compared to study done by Moberg Sköld et al [31] who reported a drop-out of 21% at the end of 3 years. The reason for such high drop-out is due to the change in schools during the promotion to the class grade and duration of the study.…”
Section: Discussioncontrasting
confidence: 66%
“…We identified 13 studies (14 reports) reporting the effectiveness of interventions in arresting or reversing noncavitated approximal lesions, with 6 studies (7 reports) that could be included in the NMA (Martignon et al 2006; Ekstrand et al 2010; Martignon et al 2010; Paris et al 2010; Martignon et al 2012; Meyer-Lueckel et al 2012; Gomez et al 2015; Table 2, Appendix Fig. 3b) and 7 that could not be pooled (Modeer et al 1984; Petersson et al 1991; Peyron et al 1992; Moberg Skold, Birkhed, et al 2005; Moberg Skold, Petersson, et al 2005; Trairatvorakul 2011; Meyer-Lueckel at al. 2016; Appendix Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The slower progression of lesions 22 , the unequal distribution of disease 2 , with about 80% of caries experience is concentrated in 20-30% of the population 10,25,31 , and the concentration of new lesions on occlusal surfaces of permanent molars 8,12,26 have also been noted.…”
Section: Introductionmentioning
confidence: 99%